PENGARUH PERAN GURU TERHADAP PEMECAHAN BARISAN DAN DERET MATEMATIKA - W Widodo; Nur Hidayanti; Indra Gunawan (Teknik Informatika Fakultas Ilmu Komputer, 2019)
This study aims to determine how quickly students' ability to respond to the material provided by the teacher and assessed through posttest questions with the category of learning outcomes given relative time according to the lesson hours and learning speed categories with a relatively faster time 30 minutes from the time of study hours. Because the mathematics learning outcomes at Serang 2 Vocational High School in Kota Serang are far from KKM expectations, in order to achieve values ​​that exceed KKM with the help of teachers who play an important role in mathematics learning. The data collection technique is done by using the learning outcomes test, while in the learning speed category it uses time in minutes to complete the learning outcomes test. In this thesis, the validity and reliability of the instrument were carried out, then using the normality and homogeneity test and two-way ANOVA test on the hypothesis test. The results of the study explain that there is an influence of the teacher's role on the speed and learning outcomes of students with two-way ANOVA analysis has a value of 5.538 Fcount greater than Ftable 3.25 which means H0 is rejected